Interpreting the Material Requirements of Recidivism: Realizing Restorative Justice in the Police Force - Achmad Fauzi; Rena Yulia; Ferry Fathurokhman; Muhammad Iqbal Ramadhan (Kosmik Hukum, 2023)
The implementation of restorative justice in the Indonesian Police Force is conducted by settling the case in the preliminary investigation and investigation stage. There are material requirements that should be fulfilled one of which is that the case is not a recidivism based on a verdict. In practice, this requirement remains unclear. For instance, an issue will arise when a perpetrator who committed a theft then settled with a restorative justice mechanism in a police station but then caught for committing another theft. The problem that emerges is whether the second offense can be still solved by restorative justice in police stations. Considering that one of the material requirements is that the case is not a recidivism according to the court’s verdict whilst restorative justice settlement is not counted as a verdict. This issue requires reinterpretation so that the implementation of restorative justice can provide justice for all parties. The purpose of this research is to re-interpret clearly material requirements in terms of not repeating criminal acts based on judicial decisions for the future implementation of restorative justice in the police station. The research method employs a normative juridical with cases approach whilst the data is analyzed descriptively to describe the material requirements in the form of not repeating a crime based on a court decision in the police stage. The results of the study reveal that in practice repetition of criminal acts must be based on court decisions. The police are still implementing restorative justice for the second criminal act with the condition that the victim and the perpetrator have reconciled. Therefore, it is necessary to deconstruct the meaning of not repeating a crime based on a court decision, so that it is not a repetition of a crime that has been resolved by means of restorative justice in the police. This is so that the recovery goals of restorative justice are achieved. Therefore, it is necessary to deconstruct the meaning of not repeating a crime based on a court decision, so that it is not a repetition of a crime that has been resolved by means of restorative justice in the police phase. This deconstruction is important to achieve restorative justice’s goals.Keywords: crime repetition, restorative justice, Indonesian police force